Pengembangan Video Animasi untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Peserta Didik Kelas VI Madrasah Ibtidaiyah - Muthia Arini Hasibuan; Nurdiana Siregar; Rora Rizky Wandini (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This research aims to find out how to develop animated video learning media to improve the mathematical problem solving abilities of class VI students. This research is based on several problems, namely students who do not understand the discussion of learning material because mathematics is considered boring and it is difficult to memorize formulas. This made students unable to solve problems in the learning process. This research used research method and development using 4D research model. The sample of this research consisted of 25 students, with the first step not using animated videos and the second step using animated videos. The research instruments used in this research were tests (essays) and questionnaires. The research results showed that the feasibility level was 92% in the "very valid" category, the practicality level was 92% in the "very practical" category, and the effectiveness level was 88.52% in the "effective" category. These results can also be seen from the pretest with an average value of 34 and posttest with an average value of 92, so the average N-Gain Score was 88.52%. So, it can be concluded that the development of animated video learning media can improve the Mathematical problem solving abilities of 6th Grade of Elementary School students.